2018
DOI: 10.1002/esp.4375
|View full text |Cite
|
Sign up to set email alerts
|

Simulating a century of soil erosion for agricultural catchment management

Abstract: Agricultural land management requires strategies to reduce impacts on soil and water resources while maintaining food production. Models that capture the effects of agricultural and conservation practices on soil erosion and sediment delivery can help to address this challenge. Historic records of climatic variability and agricultural change over the last century also offer valuable information for establishing extended baselines against which to evaluate management scenarios. Here, we present an approach that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 74 publications
(92 reference statements)
1
15
0
Order By: Relevance
“…This interpretative description of a phenomenon is key to provide understanding and insight (Bailer-Jones, 2009), which is scientifically relevant on its own. Moreover, erosion models are used to make quantitative predictions and scenariobased simulations about how soil is redistributed in potentially complex landscapes, at multiple spatial and temporal scales (e.g., Eekhout et al, 2018;Panagos et al, 2015;Prasuhn et al, 2013;Shrestha and Jetten, 2018;Smith et al, 2018). Policymakers and stakeholders might find these predictions useful, as they may help substantiate environmentally sensitive decisions regarding soil, water, and food security.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…This interpretative description of a phenomenon is key to provide understanding and insight (Bailer-Jones, 2009), which is scientifically relevant on its own. Moreover, erosion models are used to make quantitative predictions and scenariobased simulations about how soil is redistributed in potentially complex landscapes, at multiple spatial and temporal scales (e.g., Eekhout et al, 2018;Panagos et al, 2015;Prasuhn et al, 2013;Shrestha and Jetten, 2018;Smith et al, 2018). Policymakers and stakeholders might find these predictions useful, as they may help substantiate environmentally sensitive decisions regarding soil, water, and food security.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…This concept takes heterogeneities into account, which constitutes a key to improving catchment behaviour modelling (López-Vicente et al, 2013). For instance, Smith et al (2018) demonstrated that models that capture the effects of spatial and temporal variations in agricultural and conservation practices on soil erosion and sediment delivery greatly improve the model outcome and facilitate decision making regarding catchment management practices. The difficulty lies in integrating connectivity into models without over-parameterization (Heckmann et al, 2014), because highly parameterized models have operational limitations (Blöschl and Sivapalan, 1995;Lane, Nichols and Paige, 1995;Seyfried and Wilcox, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Field amalgamation due to mechanisation over time, resulting in increased field size and reduced hedgerows, likely increased hillslope soil erosion risk and modified hydrological pathways (Thomas et al, ). However, the impact of cropped field positions on modelled mean suspended sediment yield versus the window of opportunity effect has been reported as 22% and 100%, respectively (Smith et al, ). This suggests the gradual amalgamation of fields is likely to have a minor impact on soil erosion and sediment delivery, particularly considering the low connectivity of the majority of catchment soils.…”
Section: Discussionmentioning
confidence: 99%